Herbie fully loaded - Robinson, Angela (Pasig City : Viva Video, 2005)
Start your engines! The dun-lovin', free- wheelin' VW Bug with a mind all its own is back and better than ever in Disney's all-new, revved-up comedy adventure! Teen favorite Lindsay Lohan (Fraky Friday, Confessions Of A Teenage Drame Queen) teams up with Herbie in this outrageous comedy that's sure to entertain the whole family. After discovering the irresistible Herbie in a junkyard, Maggie Peyton (Lohan) restores everybody's favorite Beetle and together they go off-road... and than onto the racetrack and into the record books!